IL-7–glucose–Aiolos axis orchestrates pathogenic CD8 + T cell function in spondyloarthritis - Mitsuhiro Akiyama; Waleed Alshehri; Mirei Koroyasu; Tomohiro Kaburaki; Keiko Yoshimoto; Koichi Saito; Kanako Shimanuki; Yuko Kaneko (Proceedings of the National Academy of Sciences, 2026)
CD8 + T cells are essential mediators of host defense, whereas their aberrant activation contributes to inflammatory diseases such as spondyloarthritis. The molecular mechanisms governing human CD8 + T cell effector programming remain incompletely understood. Here, we identify a metabolically distinct subset of human CD8 + T cells defined by high expression of CXCR3, IL-7R, and GLUT1 and low expression of the transcription factor Aiolos. IL-7–JAK–STAT signaling was associated with increased GLUT1 expression and glucose uptake, accompanied by reduced Aiolos expression in CD8 + T cells. Consistent with this, Aiolos functioned as a regulatory constraint on effector cytokine production under glucose-limited conditions, and its reduction was associated with enhanced cytokine production in metabolically active CD8 + T cells. Circulating CD8 + T cells from patients with spondyloarthritis exhibited elevated GLUT1 expression compared with rheumatoid arthritis and healthy controls, which correlated with disease activity. In addition, CXCR3 + IL-7R + pSTAT5 + GLUT1 + Aiolos low CD8 + T cells were enriched in inflamed joints, where CXCL10 may contribute to their recruitment. Increased FDG uptake in inflamed sacroiliac joints further supports enhanced metabolic activity at sites of inflammation. JAK inhibitor therapy was associated with reduced GLUT1 expression and increased Aiolos expression in CD8 + T cells, accompanied by decreased effector cytokine production and clinical improvement in patients with spondyloarthritis. Together, these findings support a model in which cytokine signaling, metabolic state, and transcriptional regulation are functionally linked in human CD8 + T cells, and suggest that Aiolos may act as a regulatory node integrating these inputs in inflammatory diseases.